SOLUSI PENURUNAN DAYA BELI MATA UANG PASCA INFLASI DALAM EKONOMI SHARIâAH - Baihaqi, Baihaqi (LP2M IAIN Mataram, 2012)
The problem of declining purchasing power of the currency after inflation, has a negative effect on peopleâs lives, in terms of economic, social, and political. As a result, there will be inequity in the pending debt payments. Parties who have money will lose some wealth due to the loss of purchasing power of the money they had. On the other hand, Islamic concepts provide a solution to the problem, but it has not been widely studied. To explore this issue, the method used is descriptive normative i.e. by doing a search of the literature related to the issue of monetary economics literature both Islamic and conventional economics. The results showed that Islam has several appropriate methods to use in making payment to realize justice and avoid harm between the parties who make transaction and can prevent bad influences of inflation. Several methods can be used to avoid a decline in the value of money due to inflation, such as adjusting the value of money to the value of gold and silver, adjusting debt with fixed-value currency, doing indexation, avoiding ihtika>r practices and restore the monetary system to a standard system of gold and silver.